Acylation of indolyl subsituted β-ketonitriles. The way to new indolo[2,3-c]pyrilium and β-carboline derivatives - N. M. Bogdan; S. L. Bogza; Yu. A. Nikolyukin (Журнал органічної та фармацевтичної хімії, 2020)
Aim. To synthesize 4-cyanoindolo[2,3-c]pyrilium salts and examine their reactivity towards N-nucleophiles. Results and discussion. The acylation reaction of 2-(indolyl-3)-2-aroylacetonitriles under acid catalysis conditions was studied. 4-Cyanoindolo[2,3-c]pyrillium borofluorides were obtained, and ketonitrile enolacylates were isolated as by-products of the reaction. Treatment of the 4-cyanoindolo[2,3-c]pyrilium salts with ammonia led to 4-cyano-β-carbolines while the interaction of the salts with hydrazine hydrate resulted in formation of pyrazolo[3’,4’:5,6]pyrido[3,4‑b]indoles – derivatives of a new heterocyclic system. The latter are formed via recyclization involving the pyran ring and the cyano group. Experimental part. Upon the treatment of 2-(indolyl-3)-2-aroylacetonitriles with acetic anhydride/tetrafluoroboric acid mixture, the acylation of the indole fragment in position 2 was followed by cyclization, resulting in formation of 4-сyanoindolo[2,3-c]pyrilium salts. The reactivity of the pyrylium salts was studied on the examples of their interaction with N-nucleophiles – ammonia and hydrazine hydrate. The structure of the compounds synthesized was confirmed by 1H NMR, IR spectroscopy and elemental analysis.